2017
DOI: 10.4172/2161-1017.1000272
|View full text |Cite
|
Sign up to set email alerts
|

Major Micro vascular Complications and Associated Risk Factors among Diabetic Outpatients in Southwest Ethiopia

Abstract: Background: Diabetic complications and comorbidities, mainly due to poorly controlled diabetes, are the common causes of hospital admissions and mortalities among diabetic populations. Although studies from Ethiopia show high incidence of complications, data on associated risk factors is scarce. The current study was aimed to assess the potential risk factors contributing to microvascular diabetic complications in the study area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…This is similar to studies conducted in Arbaminch (13) and China (31). Finding from Southwest of Ethiopia showed diabetic patients who had family history diabetes were threetimes more susceptible to the development of micro vascular complications like DR (12). Diabetic patients who had poor glycemic control had higher odds of developing retinopathy than those with good glycemic control.…”
Section: Providing Proper Health Information and Counseling On The Cosupporting
confidence: 84%
See 1 more Smart Citation
“…This is similar to studies conducted in Arbaminch (13) and China (31). Finding from Southwest of Ethiopia showed diabetic patients who had family history diabetes were threetimes more susceptible to the development of micro vascular complications like DR (12). Diabetic patients who had poor glycemic control had higher odds of developing retinopathy than those with good glycemic control.…”
Section: Providing Proper Health Information and Counseling On The Cosupporting
confidence: 84%
“…Similar studies in Singapore (33), San Franscisco (38) and India (29) indicated that diabetic patients who were anemic was independently associated with an increased risk of developing DR. But cohort study done in china (15), Korea (28) and Ethiopia (12) suggested that higher hemoglobin was independently associated with an increased risk of DR. These differences could be anemia induced retinal hypoxia which alters angiogenesis, capillary permeability, vasomotor response, and cell survival and also due to low plasma ferritin concentration (11).…”
Section: Providing Proper Health Information and Counseling On The Comentioning
confidence: 97%
“…Studies from 4 regions and 1 town administrative of the country were included. Oromia [12,16,17], Amhara [19,25,26], and AA [11,15,27] contributing three studies in each region and 1 from southern nationalities [18] and 1 from Tigray [24] region ( Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…3). Accordingly, the prevalence ranged from 7.15% (95%CI: 3.73, 10.56) in Oromia region [12,16,17] to 19.31% (95%CI: 2.7. 41.37) in Addis Ababa [11,15,27].…”
Section: Subgroup Analysismentioning
confidence: 99%
See 1 more Smart Citation